63 Effect of a Novel Consensus Bacterial 6-phytase Variant on Mineral Digestibility and Bone Ash in Young Growing Pigs Fed Diets with Low and High Soluble Limestone. (7th May 2021) - Velayudhan, Deepak E; Kumar, Arun; Dersjant-Li, Yueming
Abstract: The effect of a novel consensus bacterial 6-phytase variant (PhyG) on total tract digestibility (ATTD) of minerals and bone ash was evaluated in piglets fed diets with low and high soluble limestone (LSLM and HSLM, 69 and 92% solubility at 5 min). For each limestone, 8 diets were formulated: an inorganic phosphate-free negative control (NC) diet based on wheat, corn, soybean-meal, canola-meal and rice-barn [0.18% standardized total tract digestible (STTD) P and 0.58% Ca], NC supplemented with 250, 500, 1, 000 or 2, 000 FTU/kg of PhyG, or with monocalcium phosphate (MCP) to formulate 3 positive controls with 0.21, 0.27, 0.33% STTD P, and 0.64, 0.70 and 0.75% Ca, respectively. In total 128 pigs (12.8 ± 1.33 kg, n=8) were adapted for 14 d followed by 4 d of fecal collection. Femurs were collected on the last day. Data were analyzed as one-way ANOVA and means separated by Tukey test. In addition, a 2 × 4 factorial analysis was performed to test the effect of limestone solubility at different MCP levels in control diets, a 2 × 5 factorial analysis was performed to determine the effect of limestone solubility at different phytase levels. Phytase dose-response was analyzed by orthogonal polynomial. Across phytase diets, HSLM reduced (P < 0.05) ATTD Ca and P compared with LSLM. A consistent negative effect on ATTD P was also observed with HSLM in control diets. Across limestones, increasing phytase increased (P < 0.05) ATTD Ca and P in a linear or exponential manner. Limestone solubility had no impact (P = 0.69) on bone ash. PhyG linearly increased (P < 0.05) bone ash and 250 FTU/kg of PhyG maintained bone ash compared to PC. In conclusion, limestone solubility showed a negative impact on ATTD P and Ca, the novel consensus phytase improved ATTD P and Ca regardless of limestone.